Eficiência de ensaios ecotoxicológicos na detecção de toxicidade em efluentes de refinaria de petróleo - Maffazzioli, Taísa Fedrizzi (My University, 2014)
One of the main sources of water pollution is industrial wastewater. Among these, stands the waste of oil refinery effluents because is quite complex and of difficult tractability. Therefore, it is evident the need for continuous monitoring of the quality of these effluents, since they are considered high risk waste. In addition to monitoring physical and chemical, biological monitoring is an important tool for assessing the quality of effluents. The aim of this study was to evaluate the effectiveness of four tests in determining the toxicity of treated wastewater of oil refinery. Were performed acute toxicity tests with Daphnia magna and heterotrophic aerobic bacteria (D Test), and chronic toxicity tests with Ceriodaphnia dubia and Caenorhabditis elegans. Tests with D. magna followed the NBR 12713 (ABNT, 2004) and had the mortality as endpoint. The D Test was based on Krebs (1985) and assessed the effects of stimulation or inhibition of biochemical oxygen consumption (BOD). Tests with C. dubia evaluated the mortality rate and reproduction of organisms, according to NBR 13373 (ABNT, 2005). Tests with C. elegans were performed according to ISO / DIS 10872 (2009), and had the growth and reproduction as endpoints. The five evaluated samples were from an oil refinery in the state of Parana, Brazil. The statistical analysis showed that C. elegans was the most sensitive organism to the effluent, presenting the observed effect concentration (OEC) from 12.5%, which classified it as moderately sensitive organism. Tests with C. elegans and the D Test showed low-dose stimulation, a phenomenon known as hormesis. This phenomenon should be considered in environmental assessments because every change in communities composition and structure interferes in the ecosystems integrity.
Uma das principais fontes de poluição dos recursos hídricos são os efluentes líquidos industriais. Dentre esses, destacam-se os efluentes de refinaria de petróleo, pois geram efluentes bastante complexos e de difícil tratabilidade. Desta forma, evidencia-se a necessidade de monitoramento contínuo da qualidade desses efluentes, uma vez que são considerados de alto risco. Além do monitoramento físico-químico, o monitoramento biológico é uma importante ferramenta para avaliação da qualidade de efluentes. O objetivo desse trabalho foi avaliar a eficiência de quatro ensaios na determinação da toxicidade de efluente tratado de refinaria de petróleo. Foram realizados ensaios de toxicidade aguda com Daphnia magna e com bactérias aeróbias heterotróficas (Teste D), e ensaios de toxicidade crônica com Ceriodaphnia dubia e Caenorhabditis elegans. Os ensaios com D. magna seguiram a NBR 12713 (ABNT, 2004) e tiveram como endpoint a mortalidade. O Teste D foi baseado em Krebs (1985) e avaliou efeitos de estímulo ou inibição do consumo bioquímico de oxigênio (CBO). Ensaios com C. dubia avaliaram a mortalidade e a reprodução dos organismos, segundo a NBR 13373 (ABNT, 2005). Os ensaios com C. elegans foram realizados de acordo com a ISO/DIS 10872 (2009), e tiveram o crescimento e a reprodução como endpoints. As cinco amostras avaliadas foram provenientes de refinaria de petróleo do estado do Paraná. A análise estatística dos resultados mostrou que C. elegans foi o organismo mais sensível ao efluente, apresentando concentração de efeito observado (CEO) a partir de 12,5%, sendo classificado como organismo moderadamente sensível. Os ensaios com C. elegans e o Teste D apresentaram estímulo na concentração mais baixa, fenômeno conhecido como hormese. Esse fenômeno deveria ser considerado em avaliações ambientais uma vez que toda alteração na composição e estrutura de comunidades interfere na integridade dos ecossistemas.
Keywords: Bioquímica; Água - Poluição por petróleo; Petróleo; Resíduos industriais; Oil pollution of water; Petroleum; Factory and trade waste